As políticas indigenistas no Brasil: um estudo de caso sobre o atendimento das demandas do povo guarani no municipio de Guaíra - PR - Niedermayer, Natália Raquel (2018)
This research is based on research on the subject of indigenous peoples 'rights and, based on theoretical knowledge already systematized and on practical experiences with the approach of university and external activities with indigenous peoples, based on Marx' s critical social theory , to understand how the historical, political and cultural struggle of the indigenous peoples' rights in the capitalist mode of production is expressed and the guarantee of their rights in the construction and development of the social policies inserted in the reality of the Guarani people. Scientific research, with a qualitative approach, formulates as specific objectives, present the rescue of the genesis of social policies, with a cut in the Latin American context, present the advances in the construction of social policies to meet the demands of indigenous peoples in Brazil, identify the processes of violation of the rights of the indigenous people of the Avá-Guarani nation of the west of the State of Paraná, understand the formation of indigenous territories in the municipality as well as on the enforcement and guarantee of the rights of these subjects in the municipality, given the conditions of vulnerabilities and constant violations rights to life, territory, culture, health, education, social assistance and a healthy environment. This research aims to contribute to the systematization of a theoretical and empirical reference on the rights of indigenous peoples and forms of violation of human rights, as a possibility to strengthen the struggle for the rights of these peoples and for the different areas of scientific and interventional knowledge. In order to achieve the purposes of the study, the research proposal of an exploratory nature is based on bibliographical research, documentary research and field study, having as subjects of the research the managers of the Secretariats of Social Assistance, Education, Health, and Culture of the municipality of Guaíra. The theoretical and field study presents an analysis in order to understand how the territorial condition influences the development of the actions of these secretariats, understood through concrete reality in the perspective of the totality of the presented elements, constructed within a historical and contradictory movement that does not can be denied. Starting from the following categories of analysis: social policies, indigenous peoples' rights, territory, Avá-Guarani nation. Key words: Social Policy. Indigenous peoples. Territory. Avá Guarani.